Product price image: proposition of a conceptual model (Revista de Administração, 2013)
Among the several competences attributed to organizations, price management plays an important role in strategic decision-making, profitability, and income generation. This study seeks a theoretical model to measure the product price image. Accordingly, we propose a conceptual model which results in the proposal of eighteen research hypotheses. The price image can be defined as a latent and multidimensional variable. The refinement and integration of concepts from the literature review led us to identify seven dimensions that can better measure price image: functional, positive emotion, negative emotion, symbolic, justice, axiomatic, and social. These dimensions explain customers' choices more efficiently than the simple item value for money. These dimensions of price image are connected, and consumers' involvement moderates the relationship among these dimensions and the perceived value of the product. The contributions of this paper are: first, to identify and understand the key dimensions that constitute the price image; and second, to propose a theoretical model as a basis to measure the product price image.